A Meta-frontier method of decomposing long-term construction productivity components and technological gaps at the firm level: evidence from Malaysia. Issue 2 (1st February 2019) - Azman, Mohd Azrai; Hon, Carol K. H.; Skitmore, Martin; Lee, Boon Liat; Xia, Bo
Abstract: There is a need for a better approach to measure construction productivity rigorously, multilaterally, longitudinally and decomposed into its components. In response, this paper offers a robust approach to analysing construction productivity at the firm level that has been lacking in the industry to date, by measuring the Total Factor Productivity (TFP) of 37 public-listed Malaysian construction firms over 14 years (2003–2016), based on the Färe-Primont index. In comparing different groups of building, civil and specialist construction firms, this is the first application of a meta-frontier framework to capture the technological gaps involved. Based on the construction firms' financial data, it is found that TFP improvement generally occurs due to Technical Efficiency (TE) and Scale-Mix Efficiency (SME) (largely scope economies), and significant technological gaps exist among different groups. Moreover, the industry suffered a decline in technologically related production environment over the period – prompting the conclusion that long-term policy engagement should focus on technological improvements. The paper provides a robust approach to analysing construction productivity at the firm level that also can be used for accessing productivity components and technological gaps in construction and other industries.